2016
DOI: 10.1080/17843286.2016.1252546
|View full text |Cite
|
Sign up to set email alerts
|

A case of dose escalation of quetiapine in persistent insomnia disorder

Abstract: Quetiapine, an atypical antipsychotic drug, is recommended for the treatment of schizophrenia and mood disorders. In addition, given its sedative effects, a low dose of the agent is also widely used in the treatment of anxiety disorders, personality disorders, substance abuse, and sleep disturbances. In this case study, quetiapine was the first effective drug in reducing chronic insomnia in a male patient with a long treatment history. Because its effect declined over time, in the course of two years, a gradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
(10 reference statements)
0
2
0
1
Order By: Relevance
“…Although a dose increase to 500 mg twice daily would be sufficient to ensure 30–50% of subjects attained the upper therapeutic window of 100 ng/ml (Table ), a dose increase to 700 mg twice daily was identified as satisfying the requirement to attain both the 50 and 100 ng/ml lower windows (Figure ), with attainment of >95 and >62% of subjects, respectively. While trials have suggested an upper dose of 800 mg/day, higher doses of between 800 and 2000 mg/day have been reported to be tolerated in acute and maintenance therapy. Further, sparse case reports are available of significantly higher overdoses of least 20–24 g being ingested with little acute effects …”
Section: Discussionmentioning
confidence: 99%
“…Although a dose increase to 500 mg twice daily would be sufficient to ensure 30–50% of subjects attained the upper therapeutic window of 100 ng/ml (Table ), a dose increase to 700 mg twice daily was identified as satisfying the requirement to attain both the 50 and 100 ng/ml lower windows (Figure ), with attainment of >95 and >62% of subjects, respectively. While trials have suggested an upper dose of 800 mg/day, higher doses of between 800 and 2000 mg/day have been reported to be tolerated in acute and maintenance therapy. Further, sparse case reports are available of significantly higher overdoses of least 20–24 g being ingested with little acute effects …”
Section: Discussionmentioning
confidence: 99%
“…Vi er ikke kjent med retningslinjer som tilrår bruk av kvetiapin for behandling av insomni Studier utover to uker finnes ikke, slik at langtidseffekt av lavdose kvetiapinbehandling er ukjent. Doseeskalering er rapportert ved bruk av kvetiapin mot primaer insomni, og mange pasienter rapporterer om problemer med å seponere kvetiapin etter lavdosert bruk (13). Det er også holdepunkter for at kvetiapin har misbrukspotensial (20).…”
Section: Bivirkninger Ved Bruk Av Lavdose Kvetiapinunclassified
“…When quetiapine is used to treat primary insomnia, dosage escalation has also been reported. 4,5 Well-designed study is needed to verify the effectiveness of quetiapine for insomnia in order to maximize the therapeutic effect and avoid side effects in clinical fields. It would also be beneficial to look into the impacts on specific demographics, such as the elderly, delirium, and sedative addiction.…”
mentioning
confidence: 99%